2014
DOI: 10.2147/ott.s51835
|View full text |Cite
|
Sign up to set email alerts
|

Effect of onion flavonoids on colorectal cancer with hyperlipidemia: an in vivo study

Abstract: ObjectivesThis study aims to find the effect of onion’s extraction on the colorectal cancer with hyperlipidemia.MethodWe established a hyperlipidemia-subcutaneously heterotopic colorectal cancer orthotopic transplant model and fed mice a high fat diet and performing transplantation. Animal models were treated with capecitabine and/or simvastatin and low-, middle-, high- dose of onion’s extraction and both tumor growth rate and blood lipid levels were monitored.ResultsWe found that colorectal cancer in onion’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The antihyperlipidemic property of flavonoids has equally been confirmed in cancer engendered dyslipidemia. 75 In addition to these studies, Ma et al 76 proposed the possible mechanism by which flavonoids display these therapeutic properties. They noted that the capability of flavonoids from Morus indica to normalize blood lipids and glucose concentrations of high fat diet/low dose STZ-induced hyperlipidemic and hyperglycemic rats, were in connection with the upregulation of hepatic superoxide dismutase activity, reduction of hepatic malondialdehyde content, downregulation of hepatic CYP2E1 expression, and increase of glucose transporter 4 (GLUT-4) expression in skeletal muscle of the treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…The antihyperlipidemic property of flavonoids has equally been confirmed in cancer engendered dyslipidemia. 75 In addition to these studies, Ma et al 76 proposed the possible mechanism by which flavonoids display these therapeutic properties. They noted that the capability of flavonoids from Morus indica to normalize blood lipids and glucose concentrations of high fat diet/low dose STZ-induced hyperlipidemic and hyperglycemic rats, were in connection with the upregulation of hepatic superoxide dismutase activity, reduction of hepatic malondialdehyde content, downregulation of hepatic CYP2E1 expression, and increase of glucose transporter 4 (GLUT-4) expression in skeletal muscle of the treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of a strong association between flavonoid intake and oesophageal or colorectal cancer is particularly surprising because numerous in vitro and animal studies have demonstrated an inverse association between flavonoid and oesophageal or colorectal cancer 34 35 36 37 . However, many flavonoids present in foods cannot be absorbed in their native form, including esters, glycosides, and polymers 38 .…”
Section: Discussionmentioning
confidence: 99%
“…In vivo result showed a significant reduction in the tumor growth in the mice by 38% after 2 weeks (Kim et al, 2015). Another study on onion flavonoids extract showed a promising result, whereby onion's extraction inhibits the proliferation of CRC in new established orthotopic transplant animal model (He et al, 2014). However, among all vegetables, cruciferous vegetables have received much interest due to the unique contents of high glucosinolate which can be metabolized to isothiocyanates (ITCs) and indole-3-carbinol (I3C) by myrosinaseexpressing colonic bacteria.…”
Section: Vegetablesmentioning
confidence: 98%
“…It is well established that consumption of a certain type of fruit which contains high amount of fiber, folate, vitamins, minerals and antioxidants can act as a chemo-preventive agents against CRC (Song et al, 2015). Studies on pomegranate and its bioactive products have yielded contestant and significant findings against CRC in vitro, in vivo and in clinical trials (Jaganathan et al, 2014;Molina et al, 2015).Apple and its active componentpolysaccharides has been found to reduce the DNA damage in the distal colon of dimethylhydrazine (DMH)-initiated rats, and also decrease the hyperproliferation of human colon carcinoma cells (HT-29) via induced cell-cycle block in a P53 (Li et al, 2015). Similarly, black raspberry seeds and their active constituents have successfully suppressed the growth of HT-29 cells by up upregulation of P21 and activation of caspase 3, 8 and 9 (Cho et al, 2015).…”
Section: Fruitsmentioning
confidence: 99%